DISSOLVED OXYGEN CONCENTRATION DETERMINATION (1979)
PURPOSE:To measure the concentration of dissolved oxygen in a mixed liquid in an aerating bath accurately for a long time by detecting the concentration of nitrous oxide gases in the waste gases from the aerating bath of an active sludge water treating system. CONSTITUTION:A waste water 1 is mixed in an aerating bath 2 with a returned sludge, which is partially circulated from a sedimentation basin 4 so that organic substances in the waste water are converted into sludges by tha air fed from a blower 8 and fed to the basin 4 thereby to make the active sludge water treating system. A waste gas sampling cylinder 23 is mounted in the bath 4 so that the waste gases sampled are analyzed by an infrared spectrophotometer 24 thereby to quantitize the concentration of the nitrous axide. Then the relationship, as shown in the drawing and as has been obtained by the previous measurements, between the concentration of NO2 in the waste gases and the dissolved oxygen concentration (DO) in the mixed water of the aerating bath is used to obtain the value of DO from the concentration of NO2. Incidentally, calculating circuits 26 and 27 and a control circuit 28 are used to obtain the value d of DO from the concentration n from NO2. Then, the difference DELTAg between the target value go of the aeration and the acutal value g is obtained, and an adjusting valve 29 is operated with the value obtained so that the system can be continuously controlled.